Divergent access to polycyclic spiro- and fused-N,O-ketals through Bi(OTf)3-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines and alkynols - Nakate, Ashwini K.; Kataria, Priyanka; Sambherao, Pooja I.; Krishna, Gamidi Rama; Kontham, Ravindar (Chemical Communications, 2024)
Bismuth(iii) triflate-catalyzed [4+2]-annulation of cyclic N-sulfonyl ketimines (derived from saccharin) and alkynyl alcohols (4-pentyn-1-ols and 5-hexyn-1-ols) has been reported. This cascade annulation provides a diverse array of polycyclic spiro-and-fused N,O-ketals with excellent substrate scope, good isolated yields, and diastereoselectivities under mild reaction conditions.